Transcriptome, miRNA, and degradome sequencing reveal the leaf stripe (Pyrenophora graminea) resistance genes in Tibetan hulless barley - Yue Wang; Qian Hu; Youhua Yao; Yongmei Cui; Yixiong Bai; Likun An; Xin Li; Baojun Ding; Xiaohua Yao; Kunlun Wu (BMC Plant Biology)
Abstract Barley leaf stripe, a disease mainly caused by Pyrenophora graminea (P. graminea) infection, severely affects barley yield and quality and is one of the most widespread diseases in barley production. However, little is known about the underlying molecular mechanisms of leaf stripe resistance. In this study, the transcript expression profiles of normal and infected leaves of resistant Tibetan hulless barley (Hordeum vulgare L. var. nudum Hook. f.) variety Kunlun 14 and susceptible variety Z1141 were analyzed by RNA sequencing (RNA-seq). The results showed a total of 7,669 and 5,943 differentially expressed genes (DEGs) were found in resistant and susceptible Kunlun 14 and Z1141, respectively, with 8,916 DEGs found between Kunlun 14 and Z1141. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the 8,916 DEGs identified many significantly enriched categories and pathways, of which a plant–pathogen interaction pathway, containing a total of 102 genes (100 known genes and two novel genes), was found, that was very important for the study of the leaf stripe resistance mechanism. Using RNA-seq, small RNA sequencing (miRNA-seq) combined with degradome sequencing (degradome-seq), four pairs associated with leaf-stripe miRNAs and target genes were obtained, namely Hvu-miR168-5p and Argonaute1 (HvAGO1), Hvu-novel-52 and growth-regulating factor 6 (HvGRF6), Hvu-miR6195 and chemocyanin-like protein (CLP), and Hvu-miR159b and gibberellin-dependent MYB (GAMYB). Transformation of the important target gene HvAGO1 into Arabidopsis verified that HvAGO1 could against Botrytis cinerea. Then RNA-seq and miRNA-seq of Arabidopsis transformed with overexpressed of HvAGO1 were performed. Based on the above research results, we constructed a Protein-Protein Interaction (PPI) network of barley leaf stripe resistance. This study lays the foundation for the study of the barley leaf stripe resistance mechanism and provides new targets for the genetic improvement of disease-resistant barley varieties.